2014
DOI: 10.1007/s10924-014-0683-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Defatted Rice Bran Properties for Biocomposite Production

Abstract: Commercial defatted rice bran (DRB) was characterized to produce biocomposite. DRB extracted protein plasticized with glycerol presented viscoelastic properties. The whole DRB with different amount and type of plasticizers was extruded into pellets. All extrudates presented pseudoplastic behavior as determined by capillary rheometer. Power-law index (n) and flow behavior consistency (K) of all DRB extrudates were respectively in a range of 0.30-0.32 and 1.2-3.8 x 10(4) which is closed to agro-polymer due to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
1
2
0
Order By: Relevance
“…The chemical composition of the sample was successfully evaluated, leading to similar results to those obtained by Siswanti et al [ 30 ] and Thiranan et al [ 31 ] for red and defatted rice bran. According to these research works, the majority of the sample accounts for carbohydrates; thus, the non-identified percentage of the rice bran under evaluation can be attributed to this basic food group.…”
Section: Discussionsupporting
confidence: 73%
“…The chemical composition of the sample was successfully evaluated, leading to similar results to those obtained by Siswanti et al [ 30 ] and Thiranan et al [ 31 ] for red and defatted rice bran. According to these research works, the majority of the sample accounts for carbohydrates; thus, the non-identified percentage of the rice bran under evaluation can be attributed to this basic food group.…”
Section: Discussionsupporting
confidence: 73%
“…Thus, the chemical characterization revealed a composition of 15.9% moisture, 13.4% ashes, 16.8% proteins and 27.9 and 24.2% fiber and starch, respectively. Previous studies revealed that the protein content consists mainly of variable fractions of glutelin, globulin, albumin, and prolamin, while the starch content is the mixture of two biopolymers: amylose and amylopectin [ 12 , 28 ]. However, the fiber removal process caused the lipid fraction to increase proportionally again to 5.8%.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the low solubility of these proteins, however, they first require complicated protein extraction and purification processes, , and also the use of potentially harmful solvents and additives for the production of biomaterials. To overcome these limitations, a few authors focused on valorizing protein-rich rice byproducts, such as rice bran and rice wine meal, avoiding expensive pretreatments and extraction processes, and used them as building blocks or as additives to develop edible films ,, and composite bioplastics. ,,,, For instance, the addition of rice bran microparticles into starch films allows improvement of their mechanical properties and water stability . In addition, rice bran can be processed by injection molding, and the properties of the resulting bioplastics can be tuned by the processing conditions and the addition of plasticizers, as well as by the blend components and the pretreatments of the byproduct.…”
Section: Upgrading Food Protein Waste Beyond the Food-value Chainmentioning
confidence: 99%